2019
DOI: 10.5187/jast.2019.61.5.254
|View full text |Cite
|
Sign up to set email alerts
|

In vivo nutritive value of rice feed for sheep and its application for cattle feed

Abstract: The objective of this study was to evaluate the nutritive value of polished rice (PR) vs unpolished rice (UPR) as a potential feedstuff for sheep in order to use as a replacer to corn in sheep diet, and as well as to present the application in the formulation of cattle diet. Six corriedale ewe were randomly assigned to each treatment. UPR and PR were provided as a dietary treatment together with timothy grass as a basal diet in a crossover design for two period with 15-d duration for each period. The ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Previous reports suggested that the nutritive value of agro-by-products is generally low (Yanti and Yayota 2017) and varied widely (García-Rodríguez et al, 2019). While the ber contents of the feedstuffs used in this study were relatively high as expected(Kalpanadevi et al 2018;Kim et al, 2019), the CP contents were unusually high as well, ranging between 77.3-215 g/kg DM. Of note was the CP content of rice hull which is signi cantly higher than most previous reports(Okoruwa et al, 2012…”
mentioning
confidence: 47%
“…Previous reports suggested that the nutritive value of agro-by-products is generally low (Yanti and Yayota 2017) and varied widely (García-Rodríguez et al, 2019). While the ber contents of the feedstuffs used in this study were relatively high as expected(Kalpanadevi et al 2018;Kim et al, 2019), the CP contents were unusually high as well, ranging between 77.3-215 g/kg DM. Of note was the CP content of rice hull which is signi cantly higher than most previous reports(Okoruwa et al, 2012…”
mentioning
confidence: 47%
“…Rice hulls may also be affecting the rate of degradability due to its high ber content. Kim et al, (2019), also reported that due to the high ber content digestibility in sheep was affected. This shows that the chemical composition of ingredients has varying effects on ruminal fermentation.…”
Section: In Vitro Ruminal Fermentation Kineticsmentioning
confidence: 97%
“…Because of the high grain content in dairy cow diets, replacing corn with rice in the diet of cows resulted in an increase in rumen starch digestibility, the dry ma er and starch intake decreased. The report of Kim et al [67] concluded that the maximum amount of paddy replacing corn in the sheep diet cannot exceed 91%. Ca elam et al [68] found that brown rice can reduce carcass weight, adipose tissue accumulation, and slaughtering performance of ca le compared with maize, indicating that it is not suitable to feed brown rice during ca le's growth and fa ening stages.…”
Section: Application Of Aged Brown Rice In Ruminant Feedmentioning
confidence: 99%